Technology Integration of Turkish Elementary School: Teaching Literacy Skills in the Post-COVID-19 Era - Rıdvan Ata; Kasım Yıldırım; Pelin İpek; Umut Can Ataş (Foxton Books, 2021)
This research aimed to explore the elementary school classroom teachers' perceptions of technology integration into teaching literacy skills. A total of 122 elementary school classroom teachers working at different elementary schools from the middle socioeconomic status setting, enrolled in the study voluntarily. In this study, a self-report questionnaire developed by the researchers was used. The data was analyzed using Microsoft Excel spreadsheet to get descriptive statistics (frequencies) corresponding the research questions. The research findings indicated that most of the elementary school teachers employ different perspectives, including whole language, literature-based and balanced instruction, and curriculum and related textbooks to teach literacy skills. In addition, the findings showed that teachers use technology to increase the effectiveness of teaching literacy skills and their goals of technology integration to teach literacy skills differentiate. The teachers also benefit from the social media applications and professional organizations in increasing their awareness of technology integration into teaching literacy skills. These results expand our understanding of Turkish elementary school classroom teachers' technology integration into teaching literacy skills by revealing their perceptions.